Analysis of exposure to vector-borne diseases due to flood duration, for a more complete flood hazard assessment: Llanos de Moxos, Bolivia. Issue 1 (2nd January 2018) - Moya Quiroga Gomez, Vladimir; Kure, Shuichi; Udo, Keiko; Mano, Akira
ABSTRACT: Flood hazard is usually assessed based on the hydrodynamic characteristic of flood (water depth and velocity); however, in riverine floodplains, flood events last for several days. In such cases, the long exposure to flood water may cause additional health problems. Nevertheless, usually flood hazard studies do not consider possible hazards due to flood duration. This paper presents a flood hazard assessment methodology for considering flood duration and exposure to vector-borne diseases, and compares flood hazard maps that include and neglect flood duration. Results from a two-dimensional hydrodynamic flood simulation combined with entomological concepts identify any mosquito-breeding pools. Proximity analyses based on mosquito flying range define the areas exposed to mosquitos; hence, to vector-borne diseases. Results were compared with the probability of mosquito occurrence, showing that solely the consideration of flood depth hazard leads to a false flood hazard assessment, under-predicting the flood hazard. Important cities and areas initially considered safe zones may be exposed to health hazards, due to flood duration. Inclusion of flood duration improves flood hazard assessment; hence, improves flood management plans. Maximum flood depth for oviposition (MFDO) and minimum flood duration (MFD) are important variables for defining mosquito-breeding pools. MFDO is the most uncertain variable. Discussion includes advantages in flood hazard assessment and present methodological limitations.